Hierarchical composition of reliable recombinase logic devices - Sarah Guiziou (Nature Portfolio, 2019)
Genetic logic devices allow the host cell to incorporate multiple inputs to determine output behaviour. Here the authors provide a framework for engineering reliable recombinase-based devices and demonstrate 4-input logic in a multicellular system.